Credit policy for agriculture in India: An evaluation. Supporting Indian farms the smart way. Rationalising subsidies and investments for faster, inclusive and sustainable growth - Anwarul Hoda; Prerna Terway (Indian Council for Research on International Economic Relations (ICRIER), 2015)
Rural indebtedness and dependence on private moneylenders is an age-old problem in India. For more than 100 years now, the Central Government and the Reserve Bank of India have been making efforts to enhance institutional credit in rural areas particularly to assist in agricultural operations. It began with the enactment of the Co-operative Credit Societies Act (1904) but efforts were redoubled after the nationalisation of Scheduled Commercial Banks in 1969. The aim of this paper is to evaluate the measures taken over the years and assess the extent to which they have been successful. It attempts to answer the question, "Is the agenda of expansion of institutional finance to agriculture unfinished?" The findings in the paper are inconclusive on this issue on account of contradictions in evidence: while the 2013 AIDIS survey finds that noninstitutional lenders still account for only 36 per cent of the total outstanding agricultural loan, the short-term credit from institutional sources in 2012-13 covered 100 per cent of the input cost in agriculture in that year according to the National Accounts Statistics.
Keywords: I38; Q18; Q14; 330; Agriculture; Credit; Subsidy